Energy efficiency indicators in road lighting: critical evaluation in a case study - Heredia, Sophia; Preciado, Oscar Ulises; Cabello, Alberto José; Manzano, Eduardo Roberto (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
Road lighting is a fundamental public service for the safety of pedestrians and drivers. Due to the global energy crisis and climate change, energy conservation has become a priority in any country. Road lighting should provide the required quality and quantity of illumination in the most efficient manner possible. In this work, a study of lighting conditions was carried out in an Argentinian city, and energy efficiency was evaluated based on three methods. The results and conclusions of the work provide an objective critique of the advantages and disadvantages of applying each method to measure the efficiency of an installation.